Rituximab, bendamustine and lenalidomide in patients with aggressive B‐cell lymphoma not eligible for anthracycline‐based therapy or intensive salvage chemotherapy – SAKK 38/08. (28th March 2016) - Hitz, Felicitas; Zucca, Emanuele; Pabst, Thomas; Fischer, Natalie; Cairoli, Anne; Samaras, Panagiotis; Caspar, Clemens B.; Mach, Nicolas; Krasniqi, Fatime; Schmidt, Adrian; Rothermundt, Christian; Enoiu, Milica; et al.
Abstract : An increasing number of older patients are suffering from aggressive lymphoma. Effective and more tolerable treatment regimens are urgently needed for this growing patient population. Patients with aggressive lymphoma not eligible for anthracycline‐based first‐line therapy or intensive salvage regimens were treated with the rituximab‐bendamustine‐lenalidomide (R‐BL) regimen (rituximab 375 mg/m 2 day 1, bendamustine 70 mg/m 2 d 1, 2, lenalidomide 10 mg d 1–21) for six cycles every 4 weeks. Forty‐one patients with a median age of 75 (range 40–94) years were enrolled: 33 patients had substantial co‐morbidities. 13 patients were not eligible for anthracycline‐based first‐line chemotherapy, 28 patients had relapsed/refractory disease. The primary endpoint, overall response, was achieved by 25 (61%) patients (95% confidence interval 45–76%). Grade ≥ 3 toxicity comprised haematological (59%), skin (15%), constitutional (15%) and neurological (12%) events. 9 patients died during trial treatment: 5 from lymphoma progression, 2 from toxicity, 2 with sudden death. After a median follow‐up of 25·9 (interquartile range 20·4–31·6) months, 13 patients were still alive. Median overall survival was 14·5 months. In conclusion, R‐BL can be considered a treatment option for elderly patients with treatment naïve or relapsed/refractory aggressive lymphoma not eligible for standard aggressive regimens.